(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
On this tesis we examine how these educational principles influenced Western educational reforms, particularly regarding equality, social justice, and collectivism. The study further analyzes the intersection of communist ideals with Western pedagogy, highlighting both adaptation and resistance in educational systems.